Pengembangan Media Pembelajaran Al-Quran Berbasis Game untuk Siswa Madrasah Ibtidaiyah - Raudhatun Nisa, Intan; Santi, Nani Endri; Nazliati; Saptiani; Nursiti Khodijah, Dedek (Al-Azkiya: Jurnal Pendidikan MI/SD, 2024)
The lack of teaching media that discusses tajweed material in schools causes students to have difficulty in understanding the material presented. Teaching media in the form of games is needed because primary school students still like to play in learning. The purpose of this study was to develop game-based learning media on the concept of mad thabi'i/ashli reading law material, mad wajib muttasil, and mad jaiz munfasil by using media feasibility testing from three teams of experts. The type of research used is R&D (research and development) using the ADDIE model (analysis, design, development, implementation, and evaluation). Media validation was conducted in three areas of experts, namely media, material, and language validation. Based on the results of the media validation test, the average score was 85%. In terms of media expert validation, this media is very feasible to use with an average value percentage of 85%. The material expert validation test stage obtained an average score of 96% with one revision, these results stated that this game-based learning media was very feasible to use. Then the language field validation stage obtained a value of 85 use in the learning process.